Penerapan Surat Edaran Mahkamah Agung Nomor 4 Tahun 2016 Dalam Sengketa Pembelian Tanah Yang Belum Terdaftar/Bersertifikat di Pengadilan Negeri Tanjung Balai - Haposan Sahala Raja Sinaga (Fakultas Hukum Universitas Kristen Indonesia, 2023)
There is a development in the understanding of buyers with good intentions in buying and selling land, namely with the issuance of SEMA Number 4 of 2016 concerning the Enforcement of the Formulation of the Results of the 2016 Indonesian Supreme Court Chamber Plenary Meeting as a Guideline for the Implementation of Duties for the Court. The formulation of the problem to be studied is: first, how is the formulation of the law of the civil chamber regarding the definition of a good faith buyer in the Circular Letter of the Supreme Court Number 4 of 2016. Second, how is the application of SEMA No. 4 of 2016 in Court Decisions and Judge Considerations in Case Number 11/Pdt.G/2023/PN.Tjb. This research uses normative legal research, the main object of this normative legal research is court decisions related to good faith land buyers in the Tanjung Balai District Court decision No. 11/Pdt.G/2023/PN.Tjb. The results of this study, the first: